2022
DOI: 10.1002/jia2.25866
|View full text |Cite
|
Sign up to set email alerts
|

Early pre‐exposure prophylaxis (PrEP) initiation and continuation among pregnant and postpartum women in antenatal care in Cape Town, South Africa

Abstract: Introduction Pre‐exposure prophylaxis (PrEP) is a safe and effective prevention strategy to reduce women's risk of HIV in pregnancy and postpartum. Effective PrEP protection requires daily PrEP adherence, but little is known about maternal PrEP continuation and factors that influence PrEP use. Methods The PrEP in pregnancy and postpartum (PrEP‐PP) study enrolled consenting pregnant, HIV‐negative women at first antenatal care (ANC) visit with follow‐up through 12 months postpartum. Eligible and consenting women… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 30 publications
(41 reference statements)
6
56
2
Order By: Relevance
“…When PrEP is offered to PPW in research studies, rates of uptake range but are relatively high. In two ongoing South Africa‐based cohorts, one that enrolled participants in antenatal care (ANC) [ 32 ] and one that recruited women planning for pregnancy [ 20 , 33 ], PrEP initiation rates were approximately 90% and 60%, respectively (though initiation rates appear to be lower in Kenya at 21.7% [ 34 ]). With the high utilization of ANC across SSA (78.9%) [ 35 ], these services are an opportune time to introduce PrEP and expand implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When PrEP is offered to PPW in research studies, rates of uptake range but are relatively high. In two ongoing South Africa‐based cohorts, one that enrolled participants in antenatal care (ANC) [ 32 ] and one that recruited women planning for pregnancy [ 20 , 33 ], PrEP initiation rates were approximately 90% and 60%, respectively (though initiation rates appear to be lower in Kenya at 21.7% [ 34 ]). With the high utilization of ANC across SSA (78.9%) [ 35 ], these services are an opportune time to introduce PrEP and expand implementation.…”
Section: Discussionmentioning
confidence: 99%
“…PrEP persistence, or sustained PrEP adherence over time, is crucial during pregnancy and the postpartum transition. Recent studies among PPW have reported persistence rates of 75% and 62% at 1 and 3 months post‐initiation [ 32 ]. Rates in adolescent girls and younger women who become pregnant are likely lower; only a third of adolescents and younger women in Kenya who initiated PrEP continued use after 1 month [ 34 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted surveys with participants enrolled in an observational cohort study assessing daily oral PrEP initiation and persistence among pregnant and breastfeeding women (PBFW) in Cape Town, South Africa (PrEP-PP) and an observational extension cohort of a cluster randomized trial offering daily oral PrEP among PBFW in Western Kenya (PrIMA-X)[23,24]. Eligibility criteria for PrEP-PP included: ≥16 years old, confirmed HIV-negative serostatus by a 4 th generation antigen/antibody combination HIV test (Abbott), intention to stay in Cape Town through the postpartum period, and no contraindications to PrEP use.…”
Section: Methodsmentioning
confidence: 99%
“…Daily oral tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) pre-exposure prophylaxis (PrEP) for HIV prevention is being rapidly scaled in South Africa and Kenya, and these two countries have the highest and second highest number of PrEP initiations globally[11]. Studies have reported high rates of oral PrEP uptake among pregnant and postpartum women in South Africa and Kenya[12,13]. However, the delivery of daily oral PrEP among pregnant and postpartum women is challenged by insufficient integration of PrEP provision and counseling into existing antenatal and postpartum systems[14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promise of PrEP, significant implementation challenges exist [ 14 ]. Evidence suggests that PrEP may be highly acceptable among PrEP‐naïve women, yet attrition and non‐adherence are significant challenges for women using PrEP [ 15 , 16 , 17 , 18 , 19 ]. Women in PrEP trials have had consistently poor adherence despite adherence support [ 20 ].…”
Section: Introductionmentioning
confidence: 99%